2014
DOI: 10.1248/bpb.b13-00997
|View full text |Cite
|
Sign up to set email alerts
|

3-Monoglucuronyl Glycyrrhretinic Acid Is a Possible Marker Compound Related to Licorice-Induced Pseudoaldosteronism

Abstract: One of the most common adverse effects of traditional Japanese kampo and traditional Chinese medicine is pseudoaldosteronism caused by licorice. In this review, the authors describe the mechanisms of licorice-induced pseudoaldosteronism by the pharmacokinetics of chemical constituents and its metabolites containing licorice. Glycyrrhizin (GL), the main constituent of licorice, is absorbed as glycyrrhetinic acid (GA), which is a metabolite of GL produced by enterobacteria before its release into the circulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 13 publications
2
33
0
Order By: Relevance
“…This condition is similar to the so-called "syndrome of apparent mineralocorticoid excess." 5,9,10 There have been several reports of hypertension in adult patients associated with abuse of licorice. However, the amount of licorice daily intake that makes hypertension a risk is not precisely known.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is similar to the so-called "syndrome of apparent mineralocorticoid excess." 5,9,10 There have been several reports of hypertension in adult patients associated with abuse of licorice. However, the amount of licorice daily intake that makes hypertension a risk is not precisely known.…”
Section: Discussionmentioning
confidence: 99%
“…Also, patients with essential hypertension are more sensitive to the inhibition of 11β‐HSD by licorice than normotensive subjects, and this inhibition causes more clinical symptoms in women than in men . Concerning the active component, Makino reported that 3‐monoglucuronyl‐glycyrrhetinic acid, a metabolite of glycyrrhizin, may be a genuine causative agent of licorice‐induced pseudoaldosteronism .…”
Section: Discussionmentioning
confidence: 99%
“…Further, the analgesic effect of SKT is believed to suppress the transmission of pain to the upper central nervous system by suppressing the release of substance P from the primary afferent fiber via the activation the descending inhibitory 5‐HT and NE neurons in the posterior horn of the spinal cord, and these active components are believed to be Paeoniae radix‐derived ALB and PAE . Further, whereas GA contributes to the efficacy of SKT, GA has also been thought, along with 3MGA, to be a causal component in hypokalemia . For these effects to be manifested, it is necessary at the very least for the active components to transition into the blood after SKT is orally administered.…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizae radix‐derived glycyrrhetic acid (GA), glycycoumarin (GCM), and isoliquiritigenin (ILG) are presumed to be active components, which are responsible for anticonvulsive, analgesic, and muscle‐relaxant effects, and Paeoniae radix‐derived paeoniflorin (PAE) and albiflorin (ALB) are presumed to be active components that are responsible for antinociceptive effects . In contrast, long‐term excessive ingestion of Glycyrrhizae radix is known to cause pseudoaldosteronism or hypokalemia, and it has been suggested that the causal components could be GA and glycyrrhetic acid‐3‐ O ‐monoglucuronide (3MGA), which is a metabolite of glycyrrhizic acid (GL) present in Glycyrrhizae radix …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation